The technology of computer catalogues - Striogienė, Aurelija (Information & Media, 1997)
Computer catalogues take an important place in the Library Information System. The technology of computer catalogues is changing. It is connected with computer catalogues using inter-library networking and on-line public access catalogues (OPAC) functioning. OPAC has a fundamental effect on user accessibility to library catalogues.First and foremost, the researcher has confirmed that users use OPACs when they have eschewed the card or another catalogue. OPACs can be searched from a workstation within the originating library, at a terminal elsewhere in the organization or remotely via national and even international telecommunications networks. There are three generations of OPACs.The On-line Computer Library Center (OCLC) and Project Integrated Catalog Automation (PICA) are large library cooperatives. The Lithuanian Integrated Library Information System will use the productions of OCLC and PICA in the future.
Keywords: -